2021
DOI: 10.1038/s41467-021-25177-3
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive characterization of 536 patient-derived xenograft models prioritizes candidates for targeted treatment

Abstract: Development of candidate cancer treatments is a resource-intensive process, with the research community continuing to investigate options beyond static genomic characterization. Toward this goal, we have established the genomic landscapes of 536 patient-derived xenograft (PDX) models across 25 cancer types, together with mutation, copy number, fusion, transcriptomic profiles, and NCI-MATCH arms. Compared with human tumors, PDXs typically have higher purity and fit to investigate dynamic driver events and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 95 publications
3
38
0
Order By: Relevance
“…Follow-up studies will be required to determine if the PDX model serves as a viable conduit for discovering clinically translatable biomarkers. Patient-derived xenografts of human cancer have emerged as powerful tools for clinical/translational science due to their recapitulation of many aspects of the biology of tumors derived from patients, including treatment responses, genomic mutation and copy number alterations, as well as RNA and protein expression [41][42][43] . This high degree of biological consistency with clinical samples may make PDX-bearing mice a potential discovery platform for identification of tumor-derived proteins in plasma since human sequences can be distinguished from mouse peptides using mass spectrometry 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up studies will be required to determine if the PDX model serves as a viable conduit for discovering clinically translatable biomarkers. Patient-derived xenografts of human cancer have emerged as powerful tools for clinical/translational science due to their recapitulation of many aspects of the biology of tumors derived from patients, including treatment responses, genomic mutation and copy number alterations, as well as RNA and protein expression [41][42][43] . This high degree of biological consistency with clinical samples may make PDX-bearing mice a potential discovery platform for identification of tumor-derived proteins in plasma since human sequences can be distinguished from mouse peptides using mass spectrometry 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…The PDX Development and Trial Centers Research Network have determined the genomic landscapes of over 500 patient-derived xenograft cancer models across 25 cancers, which have validated drug target results for different cancers 19 . This group is now creating patient-derived xenograft models from racially and ethnically diverse populations, which are often under-represented in preclinical studies.…”
Section: Supporting Basic Sciencementioning
confidence: 99%
“…Likewise, PDXs may not better represent the genomics of primary tumors compared to cell lines, and propagation in PDXs has been shown to distance the CNA landscapes of PDXs from those of the primary tumors from which they were derived ( 43 ). A study comparing the genomic landscapes of 536 PDX models with their parent tumors revealed high tumor purity and sub-tumor clone selection in PDXs compared to primary human tumors, high concordance of driver mutations in PDXs and their matched counterparts, and downregulation of mutated tumor suppressor genes in PDX models ( 44 ). Although PDX models do not fully recapitulate the mutation profile of the host, advancements in CRISPR are allowing for the induction of driver mutations into the host, establishing somatically engineered mouse models.…”
Section: Patient-derived Xenograftsmentioning
confidence: 99%